Analysis of Geometric Optics Misconceptions in Physics Pre-Service Teachers Based on a Four-Tier Test Reviewed by Gender and School Origin - Grecellia Mei Magdalena Dakhi; Riskan Qadar; Muliati Syam (Journal of Educational Sciences, 2026)
Misconceptions in geometric optics are a fundamental problem in physics education, particulary among pre-service teachers responsible for transmitting scientific concepts. Previous studies have mainly focuseed on general misconseptions and rarely integrated gender and school origin variables into a comprehensive analysis, especially in the context of pre-service physics teachers. This study aims to map the profile of understanding and misconceptions of geometric optics among pre-service teachers, while also examining differences based on gender and school origin. The method used is quantitative descriptive, involving 37 Physics Education students. Data were collected using a Four-Tier Diagnostic Test and analyzed through concept percentages and difference tests (t-test and Mann–Whitney). Results indicate that 66.14% of students were in the concept understanding category, while 19.86% had strong misconceptions, especially on the subconcept of concave mirrors. Descriptively, female students and students from urban areas showed higher understanding than male students and students from rural areas, although no statistically significant differences were found. These results expand the literature on optical misconceptions by revealing conceptual patterns influenced by students' background characteristics. These results highlight the need for adaptive learning strategies, including visual-spatial approaches and interactive simulations.